Multidecadal estimation of hydrological contribution and glacier mass balance in the semi-arid Andes based on physically based modeling and geodetic mass balance - Mejías, Alonso; McPhee, James; Mahmoud, Hazem; Farías-Barahona, David; Kinnard, Christophe; MacDonell, Shelley; Montserrat, Santiago; Somos-Valenzuela, Marcelo; Fernandez, Alfonso (Frontiers in Earth Science, 2025)
Glaciers are of paramount importance in diverse environments, and due to the accelerated retreat experienced in recent decades, efforts have intensified to achieve a comprehensive understanding of key variables such as mass balance and glacial melting. However, the scarcity of data in regions that are difficult to access, such as the Andes Cordillera, hinders reliable glaciological studies of the historical period. This study examined the mass balance and melting dynamics of the Universidad Glacier, the largest in the semi-arid Andes, from 1955 to 2020, using the physically based Cold Regions Hydrological Model (CRHM). The model was calibrated with geodetic mass balance estimates available between 1955 and 2020 and evaluated against on-site observations available between 2012 and 2014. Change point analysis revealed three contrasting periods of mass balance evolution: significant mass loss for the periods 1955–1971 and 2006–2020 and near-equilibrium mass balance from 1971 to 2006. These loss and gain periods align with the negative phases of the Pacific Decadal Oscillation (PDO) and the positive ENSO (El Niño) events, respectively. Simulated runoff from glacier melt showed a positive trend of 8% per decade since 1971. Calibrated and uncalibrated versions of the model showed similar temporal variability, but cumulative mass balance differed significantly. The model calibrated from 1955 to 2020 had a minimal overestimation of 0.1% in mass loss and slightly improved the representation of the annual albedo. Relative to this best-performing model, the model calibrated with geodetic mass balance estimates from 2000 to 2020 overestimated mass loss by 25%, whereas the uncalibrated model overestimated mass balance by 62%. Physically based modeling with parameters adjusted based on field observations is adequate to reproduce the most salient features of MB interannual variability. However, long-term projections may diverge significantly, and albedo parameterizations, including its spatial and temporal evolution throughout a glacier surface, are an avenue for future research.